O papel dos marcadores discursivos na escrita e na fala: uma taxonomia textual e interpessoal sob o enfoque da linguística sistêmico-funcional - Silva, Leila Cristina da (2010)
One of the factors that negatively interfere in text productions which are considered unsatisfying is the unfamiliarity, by writers, with the oral modality lexicogrammar which differs from that of the written modality and the fact that specific genres of speech require specific language choices. As a result and based on the fact that the oral modality is acquired before the written modality, it is not surprising that several features of the oral text end up permeating the written text, marking it with oral nuances. One of such features concerns the discourse markers (DMs). By the way, there is much controversy about the meaning of the expression discourse markers . Thus, to Taboada (2006), the first difficulty concerning the DMs is exactly defining what they are and what to call them. Hempel e Degand (2008) have studied such markers which they name frame marker or organization metadiscourse marker, based upon the textual metadiscourse classification (HYLAND; TSE, 2004: 169). Thompson and Thetela (1995), examining the interpersonal metafunction (HALLIDAY, 1994), propose to divide such metafunction into three functions: (a) personal, the writer´s stance; (b) interactional, the carrying of relations between reader and writer and (c) interactive, having tools that lead the reader through the text, thus considered as an interpersonal element. Halliday, however, would consider it part of the textual metafunction. The objective of this dissertation is examining the occurrences of organization textual discourse markers (TDMs) and interpersonal discourse markers (IDMs) in Portuguese in oral and written texts, according to Dafouz-Milne (2008), based on the classification of Hyland e and Tse (2004). Therefore, it must answer the following questions: (1) what are the TDMs and IDMs that mostly occur in the oral and written modalities? (2) How can these occurrences help to understand the syntax characteristics of these modalities? The corpus of this research is composed by an interview made by Projeto Nurc and by an opinion article published by Folha de São Paulo. The research is supported by Systemic Functional Linguistics, an approach that tries develop a theory about language as a social process and a methodology that allows a detailed description systematic description of the linguistic patterns